Silencing of CrNPR1 and CrNPR3 Alters Plant Susceptibility to Periwinkle Leaf Yellowing Phytoplasma - Sung, Yi-Chang; Lin, Chan-Pin; Hsu, Hui-Ju; Chen, Yu-Ling; Chen, Jen-Chih (Frontiers in Plant Science, 2019)
Phytoplasmas are prokaryotic plant pathogens that cause considerable loss in many economically important crops, and an increasing number of phytoplasma diseases are being reported on new hosts. Knowledge of plant defense mechanisms against such pathogens should help to improve strategies for controlling these diseases. Salicylic acid (SA)-mediated defense may play an important role in defense against phytoplasmas. Here, we report that SA accumulated in Madagascar periwinkle (Catharanthus roseus) infected with periwinkle leaf yellowing phytoplasma. CrPR1a expression was induced in both symptomatic and non-symptomatic tissues of plants exhibiting periwinkle leaf yellowing. NPR1 plays a central role in SA signaling, and two NPR1 homologs, CrNPR1 and CrNPR3, were identified from a periwinkle transcriptome database. Silencing of CrNPR1, but not CrNPR3, significantly repressed CrPR1a induction in Tobacco rattle virus-infected periwinkle plants. In addition, symptoms of periwinkle leaf yellowing progressed fastest in CrNPR1-silenced plants and slowest in CrNPR3-silenced plants. Consistently, expression of CrNPR1, but not CrNPR3, was induced by phytoplasma infection as well as SA treatment. This study highlights the importance of NPR1- and SA-mediated defense against phytoplasma in periwinkle and offers insight into plant-phytoplasma interactions to improve disease control strategies.